BLOCKCHAIN TECHNOLOGY IN FINANCIAL SERVICES : OPPORTUNITIES AND CHALLENGES IN UZBEKISTAN - Marjona Esojonova, (Ustozlar uchun, 2025)
This paper examines the adoption of blockchain in Uzbekistan’s financial sector, analyzing its potential to address challenges such as financial exclusion, fraud, and inefficiencies. Through a qualitative review of recent initiatives, regulatory frameworks, and stakeholder perspectives, the study identifies opportunities and barriers to blockchain integration.